Psychometric validation of a novel community norms measure among youth, Eswatini Violence Against Children and Youth Survey, 2022 - Stephanie Spaid Miedema; Greta M. Massetti; Francis B. Annor; Laura F. Chiang; Rebecka Lundgren; Anita Raj (PLoS ONE, 2026)
Social norms define what is acceptable and appropriate for women and men, boys and girls, in a given group or society. Restrictive social norms around women and men’s roles and responsibilities have proven harmful for both women and men, particularly in adolescence and young adulthood, and are associated with increased risk of violence. In global settings, measurement of social norms tends to rely on proxy measures capturing attitudes, beliefs, and perspectives. Measurement of social norms on women’s and men’s roles and responsibilities is particularly limited among adolescents and young adults, a formative age period where sanctions for non-adherence to norms can be heavy. We used data from the nationally representative 2022 Eswatini Violence Against Children and Youth Survey (VACS) to test the psychometric properties of a novel set of social norms survey items among male and female youth aged 13−24 (n = 7,709). Items were largely derived from prior scales and adapted by social norms experts to ensure that they were salient to the lives of adolescents in low-income settings. The items captured norms about women and men’s, boys’ and girls’ education, domestic labor, household decision-making, work, marriage and violence, with the community as the reference group. We conducted exploratory (EFA) and confirmatory factor analysis (CFA) on 16 norms survey items using split-random half samples. We identified a single-factor, four-item scale as the best-fitting solution (EFA: RMSEA = 0.060, CFI = 0.974, TLI = 0.923, SRMR = 0.076; CFA: RMSEA = 0.063, CFI = 0.972; TLI = 0.915; SRMR = 0.048). The scale captured norms in communities on domestic labor for youth and household-decision making by adults. We assessed measurement invariance by age and sex of this final one-factor, four-item solution. We observed latent mean differences by sex in baseline (β = 0.309, p < 0.001) and final DIF-adjusted (β = 0.299, p < 0.001) models. In addition, females and males varied in their propensity to endorse two of the scale items (Item 5: β = 0.225 p < 0.001; Item 6: β = −0.212, p < 0.001). We assessed correlation between the final DIF-adjusted community norms measure and two attitude scales: attitudes toward IPV ( r = 0.363, p < 0.001) and attitudes toward women and men’s relations ( r = 0.087, p = 0.018). The measure demonstrated adequate reliability and convergent validity. The analysis resulted in a promising single factor, four-item social norms scale, which meets requirements of a brief, theory-based measure and is feasible to incorporate into national and cross-national surveys. Future work is needed to validate the scale in other settings.